Structure, stoichiometry, and properties of the chimney-ladder phases Ru2Ge3+x (0 < x < 1) - Hayward, M; Ramirez, A; Cava, R (2002)
The preparation and physical characterization of non-stoichiometric Ru2Ge3+x (0 ≤ x ≤ 1) are reported for the first time. The defect TiSi2-type chimney-ladder structure is maintained for the full stoichiometry range. The resistivity of Ru2Ge3+x increases systematically with x from 300 m Ω cm, x = 0-3 Ω cm, x = 1 at 300 K. The temperature dependence is consistent with a variable range-hopping mechanism for x ≥ 0.6. The Seebeck coefficients of samples do not evolve simply with x. A low thermal conductivity (κ300 K = 0.03 W/K cm) suggests that Ru2Ge3 has some of the properties of a phonon-glass-electron-crystal. The low value of the thermoelectric figure of merit ZT = 3.2 × 10-3 (T = 300 K) calculated for Ru2Ge3 is due primarily to a low conductivity. © 2002 Elsevier Science (USA).